Game Design for Good: Using Interactive Media to Drive Sustainable Development and Social Impact - Xie Li; Wolnough Cale; Mahon Nitin (Journal of Social Entrepreneurship and Creative Technology, 2024)
The increasing popularity of interactive media, particularly video games, presents a unique opportunity to address global challenges. By integrating elements of game design with sustainable development goals (SDGs), it is possible to create engaging experiences that drive positive social impact. This study explores the potential of game design to contribute to sustainable development and social impact. The primary objective of this research is to investigate how interactive media, specifically video games, can be designed to promote sustainable development and foster social impact. The study aims to identify key design elements that effectively engage players and encourage behaviors aligned with the SDGs. This research adopts a mixed-methods approach, combining quantitative and qualitative data. A literature review was conducted to understand existing frameworks and theories related to game design and sustainability. This was followed by the development of a prototype game incorporating these principles. The game was tested with a sample of 100 participants through surveys and focus group discussions to gather insights on player engagement and behavioral impact. The findings indicate that well-designed interactive media can significantly raise awareness and influence behaviors related to sustainable development. Participants reported increased knowledge and motivation to engage in activities supporting the SDGs. Key design elements such as immersive storytelling, rewarding systems, and collaborative challenges were identified as crucial in driving player engagement and social impact. The study concludes that interactive media, especially video games, hold substantial potential in promoting sustainable development and social impact. By incorporating strategic design elements, game developers can create compelling experiences that not only entertain but also educate and inspire positive change.